Survival and Germination of Bacillus clausii UBBC07 Spores in in vitro Human Gastrointestinal Tract Simulation Model and Evaluation of Clausin Production - Ahire, Jayesh J.; Kashikar, Megha S.; Madempudi, Ratna Sudha (Frontiers in Microbiology, 2020)
Bacillus clausii UBBC07 is a commercial spore probiotic known to reduce diarrhea in childrens and adults. In the present study, survival and germination of UBBC07 spores was investigated under fed and fasted conditions in Simulator of Human Intestinal Microbial Ecosystem (SHIME). Besides this, lantibiotic production, purification and characterization was performed. The agar plate analysis showed that spores were 100% tolerant to fed and fasted gastrointestinal tract (GIT) conditions. Simultaneously, flow cytometry revealed that at the end of small intestinal incubation, 120% (fed) and 133% (fasted) spores were in viable germinating state. The transformation of viable germinating spores into viable vegetative cells was observed at 3 h of incubation under fasted GIT conditions. In antimicrobial evaluation, UBBC07 produced low molecular weight (2107.94 Da) class I lantibiotic clausin. The presence of lanB, lanC, and lanD genes confirm the clausin production. Clausin is stable at proteases (pepsin, proteinase K and trypsin), temperature (up to 100 oC) and pH (up to 11). Furthermore, the antimicrobial activity towards Gram-positive bacteria including C. difficile is advantageous. In conclusion, B. clausii UBBC07 spore probiotic is capable to survive and germinate under in vitro upper GIT conditions. The clausin production justify strains applicability in diarrhea.